MASCULINITY TRAITS BY THE MAIN CHARACTER MAUD WATTS IN THE FILM “SUFFRAGETTE” - Nurul Anugra Febriyanti; Sahril Nur; Abd Halim (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
Suffragette is a film that tells about a women's movement that fights for equal rights with men. This research aims to prove that women can also have masculinity traits in themselves through Maud Watts as one of the main characters in the film Suffragette. In this research, researchers used qualitative research methods with content analysis methods. As a method of collecting data for this, the researchers made observations. First step is to watch and read the film script of Suffragette film. Then the researchers collect data that prove Maud Watts masculinity. Last is connect all the data that the researcher has obtained with the theory of masculinity traits. The main findings in this research are indicators of masculinity and representation of masculinity through Maud Watts.This research proves that Maud Watts is a woman whose physical appearance, handling emotions and behavior are the same as men. Maud Watts dresses like a man, she also smokes to calm her mind like a man, she is also easy to make decisions, decisive, dare to take risks and also easy to make decisions and she is also a woman who is responsible like a man's nature. Besides that, Maud Watts is able to represent the characteristics of masculinity that exist in her through some of her dominant characteristics, namely hard worker, acting as a leader and also independent. This research is about analyzing the characteristics of masculinity that exist in Maud Watts as one of the female rights fighters in this Suffragette film.Keywords:Masculinity Trait, Character, Film.